The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3928/00220124-20140625-09
|View full text |Cite
|
Sign up to set email alerts
|

Precordial Electrode Placement Accuracy by Nurses in a Large Midwestern Tertiary Care Hospital

Abstract: A quality improvement project to increase the knowledge of nurses and the accuracy of electrocardiogram precordial lead placement among intensive care unit and progressive care unit staff was conducted using a single-group, pretest-posttest preexperimental design. Educational interventions based on the theory of planned behavior were developed from focus group data. A tip card, poster, and video were sequentially presented to more than 1,600 nurses. This resulted in statistically significant gains in both know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Others who evaluated the 5-electrode Mason-Likar system for continuous monitoring, reported similar results, including a low rate of correct V lead placement. 4,27 The interventions in these studies were similar to ours and included education and auditing of electrode placement with real-time feedback by unit champions 4 and tip cards and posters. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Others who evaluated the 5-electrode Mason-Likar system for continuous monitoring, reported similar results, including a low rate of correct V lead placement. 4,27 The interventions in these studies were similar to ours and included education and auditing of electrode placement with real-time feedback by unit champions 4 and tip cards and posters. 27 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to knowledge and skills, attitude is also important in nurses' competency in ECG interpretation. Several studies in this review reported nurses' negative attitudes around ECG interpretation, affecting their competency in this important nursing role (Drew et al, 1991;Nickasch, 2016;Wirt et al, 2014). Positive attitudes can motivate nurses' self-directed learning and promote their application of knowledge and skills into practice (Zhou et al, 2012); hence, negative attitudes need to be addressed.…”
Section: Discussionmentioning
confidence: 93%
“…Other causes for the negative attitudes were lack of knowledge and confidence in ECG interpretation. All these suggest that there is an urgent need to develop standardized education programs that improve nurses’ knowledge, skills and attitudes towards ECG interpretation, thereby meeting critical safety points (Fålun et al, 2020; Nickasch, 2016; Wirt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations